Palliative care nurses' strategies when working in private homes—A photo‐elicitation study. Issue 1 (7th October 2019) - Alvariza, Anette; Mjörnberg, Maria; Goliath, Ida
Abstract: Aims and objectives: To explore palliative care nurses' work experiences caring for patients at the end of life in private homes. Background: The home continues to be a desired place for care and dying; however, professional competence is needed and specialist palliative care nurses play a crucial role, often highly valued by patients and their family members. The private home as a physical work environment for nurses is explored, with both positive and negative aspects being described. To ensure future high‐quality end‐of‐life care, there is a need to describe how palliative care nurses work in private homes. Design: Interpretative descriptive. Methods: Participant‐generated photographs were used in conjunction with follow‐up interviews with ten palliative home care nurses. Interpretive description was used for analysis. This study follows the COREQ checklist. Results: The analysis process resulted in four constructed themes, presented here as strategies used by palliative care nurses: adjusting interactions and actions depending on the environment when entering each unique private home; supporting patients and family members in finding a balance between self‐care, independence and safe care; guiding patients and family members towards and through environmental changes supporting end‐of‐life care at home; and using transitions between homes to reflect, recuperate and prepare. Conclusion: Working as a palliative care nurse in private homes clearly requires a variety of skills and competences, here operationalised in different strategies used to promote high‐quality care. Relevance to clinical practice: Palliative care nurses' considerations, insights and competence when performing end‐of‐life care in the diverse environments of private homes can contribute to the development of clinical practice. Knowledge about strategies can be used in nursing practice during everyday work, in nursing education and in the organisation of care, and can inform policy to ensure future high‐quality palliative home care.